Generation of ultrashort keV Ar+ ion pulses via femtosecond laser photoionization. (15th March 2021) - Golombek, Alexander; Breuer, Lars; Danzig, Lisa; Kucharczyk, Paul; Schleberger, Marika; Sokolowski-Tinten, Klaus; Wucher, Andreas
Abstract: Ion beams with energies in the keV regime are widely utilized in solid-state physics, but the ultrafast dynamics triggered by an ion impact onto a solid surface is to date exclusively accessible via simulations based on many untested assumptions and model parameters. A possible experimental access rests on the availability of a laser-synchronized ion source delivering sufficiently short ion pulses for time resolved pump–probe experiments. Here, we demonstrate a new miniaturized ion optical bunching setup for the creation of rare gas ion pulses using strong-field femtosecond laser photoionization. Neutral Ar gas atoms at room temperature are intercepted by a 50 fs, 800 nm laser pulse focused to ∼10 μ m spot size. We demonstrate the generation of monoenergetic 2 keV Ar + ion pulses with 180 ps duration (FWHM) at laser peak intensities around 10 14 W cm −2 and of multiply charged Ar q + ions ( q = 1–5) at higher laser intensities. The results are in good agreement with detailed ion trajectory simulations, which show that the temporal resolution is essentially limited by the initial (thermal) velocity spread of the generated photo-ions, indicating the possibility to achieve even better time resolution by cooling the gas prior to ionization.